Pengaruh Budaya Organisasi dan Self Efficacy terhadap Kinerja Karyawan pada PT. PLN (Persero) Kantor Wilayah Sumatera Barat - Sarianti, Rini; Fitria, Yuki; Umairah, Dira (Jurnal Kajian Manajemen Bisnis, 2016)
This study aims to examine: (1) The influence of organizational culture on employee performance in At PT PLN (Persero) Regional Office of West Sumatra, and (2) the effect of self-efficacy on the performance of employees at PT PLN (Persero) Regional Office of West Sumatra.The research was conducted on At PT PLN (Persero) Regional Office of West Sumatra. This type of research is descriptive causative. The population in this research were 141 employees and sampled in this study as many as 104 employees. The sampling technique used was propotional cluster sampling. Data used in this study are primary data and secondary data. Data were analyzed using multiple regression analysis using SPSS 20. The results showed (1) organizational culture significantly influence employee performance in PT PLN (Persero) Regional Office of West Sumatra, (2) self-efficacy have a significant effect on the performance of employees at PT PLN (Persero) Regional Office of West Sumatra.Â